2006
DOI: 10.1210/en.2006-0171
|View full text |Cite
|
Sign up to set email alerts
|

Insulin-Like Growth Factor Binding Protein (IGFBP-1) Involvement in Intrauterine Growth Retardation: Study on IGFBP-1 Overexpressing Transgenic Mice

Abstract: In humans, intrauterine growth retardation is correlated to high levels of serum IGF binding protein-1 (IGFBP-1). This present study analyzes in vivo the impact of circulating IGFBP-1 on body growth associated to bone mineralization and carbohydrate resources. Transgenic mice used in this work overexpressed human IGFBP-1 in liver from embryonic day (E)14.5, concomitantly to the appearance of ossification centers, through to adulthood. Growth retardation was observed as early as E17.5 in homozygous (HM) mice be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
43
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(45 citation statements)
references
References 46 publications
2
43
0
Order By: Relevance
“…In a follow-up study [9], intrauterine growth retardation was in fact observed in homozygous IGFBP-1 transgenic mice at embryonic day 17.5. In homozygous mice, increased perinatal mortality was observed, which was probably due to decreased carbohydrate pools in the transgenic mice.…”
Section: Igfbp-1mentioning
confidence: 96%
“…In a follow-up study [9], intrauterine growth retardation was in fact observed in homozygous IGFBP-1 transgenic mice at embryonic day 17.5. In homozygous mice, increased perinatal mortality was observed, which was probably due to decreased carbohydrate pools in the transgenic mice.…”
Section: Igfbp-1mentioning
confidence: 96%
“…The biological relevance of high levels of IGFBP-1 has been extensively studied using transgenic technology. A dominant feature of the transgenic lines is the fetal and postnatal growth restrictions [10,11] and alterations of female reproductive functions [12,13]. Some transgenic lines also display impaired glucose homeostasis [14].…”
Section: Introductionmentioning
confidence: 99%
“…This is of importance because the activity of secreted IGF ligands is regulated by a variety of IGF-binding proteins in vivo (26), and IGF-binding proteins are also abnormally regulated in different models of IUGR (18 -21). Therefore, our studies establish that alterations in tissue expression of IGF and insulin are associated with decreased activation of their cognate receptors in fetal organs affected by IUGR.…”
Section: Discussionmentioning
confidence: 99%
“…However, there has been no systematic analysis of IGF-I or IGF-II expression in other organs affected by IUGR. Moreover, complex interactions with a variety of IGF-binding proteins regulate bioavailability and net activity of IGF ligands in vivo (26). Because these factors are also abnormally regulated in different models of IUGR (18 -21), the net effect of decreasing circulating and/or hepatic IGF-I on IGF-IR signaling are unknown.…”
mentioning
confidence: 99%